Research on Improving Optical Field Distribution of TOSA Based on 3D Defocusing Coupling - Xinhui Ding; Shi Dong; Jing Jiang (Applied Sciences, 2022)
The four-direction performance of a TOSA and power tested with different jumpers are affected by the optical field distribution of the TOSA. In order to improve the optical field distribution of a TOSA, this paper analyzes the factors affecting optical field distribution in the core and cladding of fiber and establishes a 3D defocusing coupling model to improve the uniform distribution of the optical field. The verification between the 2D coupling model and 3D defocusing coupling model shows that four-direction performance with 3D defocusing coupling is less than 1.0 dB, and the difference of power tested with different jumpers is not more than 0.5 dB. The results are better than that of a TOSA with a conventional coupling model, and the reliability and yield of the TOSA are higher. The 3D defocusing coupling model has practical guiding significance and economic value in TOSA production.